Radical-mediated thiol–ene ‘click’ reactions in deep eutectic solvents for bioconjugation - Scanlan, Eoin (My University, 2022)
Herein, we report the first application of deep eutectic solvents (DESs) in radical-mediated hydrothiolation reactions. Under UV and atmospheric-oxygen mediated conditions, the thiol–ene reac tion was applied to amino acid and peptide ligation in DESs. The conditions facilitate highly-efficient synthesis of biomolecular targets using a ‘green’ methodology, with complete recycling of the reaction medium. Fluorescent labelling and glycosylation of a minimal sequence mimetic of angiotensin-converting enzyme 2 capable of binding the SARS-CoV-2 spike protein is demonstrated for applications in the study of inhibition of COVID-19 infectivity
Keywords: COVID-19 infectivity; deep eutectic solvents; ‘green’ methodology